A Review of The Regional Tax Budget Setting For Kepulauan Selayar Regency in 2023 - Aspa Ansyarif Khalid; Muchriana Muchram (Green Publisher Indonesia, 2025)
This article discusses the analysis of the regional tax budget and regional levies in Selayar Islands Regency in 2023. This study aims to examine the determination of regional tax targets and regional levies in the 2023 Regional Revenue and Expenditure Budget (APBD) of Selayar Islands Regency based on Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. The research method used is a qualitative descriptive method by analyzing secondary data in the form of the 2023 Selayar Islands Regency Budget. The results of the study show that the determination of regional tax and regional levy targets in the 2023 Selayar Islands Regency Budget has taken into account regional macroeconomic policies, the potential for regional taxes and regional levies, the provision of relief, reduction, exemption, and postponement of payments on the principal and/or sanctions of regional taxes and regional levies, as well as national fiscal policies and fiscal incentives carried out to support investment ease policies. However, there are still obstacles in the realization of the local government budget that need to be further evaluated.